Both non-coated and polyelectrolytically-coated intraocular collagen-alginate composite gels enhanced photoreceptor survival in retinal degeneration. (February 2023) - Wong, Francisca Siu Yin; Tsang, Ken Kin; Chan, Barbara Pui; Lo, Amy Cheuk Yin
Abstract: Treatments of vision-threatening retinal diseases are often hampered by drug delivery difficulties. Polyelectrolytically-coated alginate encapsulated-cell therapy (ECT) systems have shown therapeutic efficacy through prolonged in vivo drug delivery but still face various biocompatibility, viability, drug delivery and mechanical stability issues in clinical trials. Here, novel, injectable alginate-poly-l -lysine (AP)-coated composite alginate-collagen (CAC) ECT gels were developed for sustained ocular drug delivery, and their long-term performance was compared with non-coated CAC ECT gels. All optimised AP-coated gels (AP1- and AP5.5-CAC ECT: 2 mg/ml collagen, 1.5% high molecular weight alginate, 50, 000 cells/gel, with 0.01% or 0.05% poly-l -lysine coating for 5 min, followed by 0.15% alginate coating) and non-coated gels showed effective cell proliferation control, cell viability support and continuous delivery of bioactive glial cell-derived neurotrophic factor (GDNF) with no significant gel degradation in vitro and in rat vitreous. Most importantly, intravitreally injected gels demonstrated therapeutic efficacy in Royal College of Surgeons rats with retinal degeneration, resulting in reduced photoreceptor apoptosis and retinal function loss. At 6 months post-implantation, no host-tissue attachment or ingrowth was detected on the retrieved gels. Non-coated gels were mechanically more stable than AP5.5-coated ones under the current cell loading. This study demonstrated that both coated and non-coated ECT gels can serve as well-controlled, sustained drug delivery platforms for treating posterior eye diseases without immunosuppression.